EVALUASI KURIKULUM PELATIHAN DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PAI DI BALAI DIKLAT KEAGAMAAN JAKARTA - Bahrissalim, Bahrissalim; Fauzan, Fauzan (EDUKASIA, 2018)
This study aims to analyze the curriculum of PAI SD teacher training at Jakarta Religious Training Center, to identify the qualifications of the teaching staff and the Training participants at the Jakarta Religious Training Center, to review the implementation process of the curriculum at the Jakarta Religious Training Center, and to analyze the results of the improvement of pedagogic competence after the participants attended the training. The method used in this research is survey method using evaluative research type with CIPP model (context, Input, Process, Product). Data collection techniques used were observation, interview, questionnaire, document analysis and test. This research found: 1) Design of curriculum Training of Islamic Primary School Education teachers need to be improved formulation of training objectives and competence of Training participants, 2) Teachers Training of Islamic Primary School Teachers Education teachers meet the qualifications determined by R & D Institute of Ministry of Religious Affairs. 3) The qualification of the participants of the Teacher Training for Islamic Primary School Education is not in accordance with the stipulations set out by the IAARD and the Ministry of Religious Affairs, 4) The evaluation of post-training process and evaluation needs to be improved and supplemented with monitoring and evaluation, and mentoring program. 5) The process of education and training at Jakarta Religious Training Center can improve the competence of teachers of Islamic Religious Education of Elementary School in DKI Jakarta.